(untitled) (Palimpsesto, 2021)
One of the greatest challenges that society faces and that has been taken as a primary axis by the different governments of the world and specifically that of Mexico is education; Education as an ideal means to prepare, direct and face this new 21st century society and take it towards the knowledge society. This is one of the most important current challenges, since education is the vehicle that will lead to successfully face it.